Pengaruh Good Corporate Governance terhadap Kinerja PT Tonasa Lines - Sitti Hajar Damayanti; Muhammad Yahya; Abdul Karim (Bata Ilyas Journal of Accounting, 2020)
The purpose of this study is to determine how much influence the principles of Good Corporate Governance have on the performance of PT. Tonasa Lines. The results of this study reveal that not all principles of Good Corporate Governance affect the performance of PT. Tonasa Lines. As the principles of Transparency and Accountabillity have a positive but insignificant effect on company performance, the principles of Responsibillity has a negative and insignificant effect on company performance, while those that support company improvement are only the principles of Independence and Iairness which have a positive and significant effect on improving company performance, in this case PT. Tonasa Lines.